2022
DOI: 10.3390/buildings12122216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cleaning and Disinfection Product Use, Glove Use, and Skin Disorders by Healthcare Occupations in a Midwestern Healthcare Facility

Abstract: Healthcare facility staff use a wide variety of cleaning and disinfecting products during their daily operations, many of which are associated with respiratory or skin irritation or sensitization with repeated exposure. The objective of this study was to characterize the prevalence of cleaning and disinfection product use, glove use during cleaning and disinfection, and skin/allergy symptoms by occupation and identify the factors influencing glove use among the healthcare facility staff. A questionnaire was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Studies have reported that wearing personal protective equipment (PPE) is protective against chemicals found in ingredients in some CSDPs. Henn et al reported about 9% of participants did not always wear gloves when using disinfectants, while Humann et al reported that the proportion of time when gloves were used increased when chemical products were used, although this change varied based on occupation [24][25][26]. Another study reported that about 80% of teachers did not wear gloves when cleaning or disinfecting their classrooms [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that wearing personal protective equipment (PPE) is protective against chemicals found in ingredients in some CSDPs. Henn et al reported about 9% of participants did not always wear gloves when using disinfectants, while Humann et al reported that the proportion of time when gloves were used increased when chemical products were used, although this change varied based on occupation [24][25][26]. Another study reported that about 80% of teachers did not wear gloves when cleaning or disinfecting their classrooms [2].…”
Section: Introductionmentioning
confidence: 99%